Performance of Hybrid Asphalt Mixture through the Stability and Tensile Strength - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; K. A., Masri (Bentham Open, 2023)
Introduction: The stability and tensile strength of asphalt mixtures play a crucial role in pavement durability, primarily due to the challenges associated with cracking. This study investigates the utilization of a hybrid asphalt mixture comprising hybrid materials: Palm Oil Fuel Ash (POFA), garnet waste and sawdust to enhance the modified asphalt performance. Aims: The objective is to examine the hybrid materials’ influence towards the mechanical properties of the hybrid asphalt mixture, specifically focusing on the Indirect Tensile Strength (ITS) as well as the Marshall stability test. Methods: To achieve this, hybrid materials were finely ground and sieved to 25µm before being incorporated into the mixture. The Marshall mix design procedure was conducted, utilizing hybrid binders at concentrations of 0% (control), 3% 6%, and 9%. The effects of the hybrid asphalt mixture on stability, flow, stiffness, and ITS were assessed at the optimal binder content. Results: The findings indicate that the hybrid asphalt mixture reveals enhanced Marshall stability, stiffness, flow, and ITS values compared to conventional asphalt mixtures. Notably, hybrid asphalt mixtures with 6% binder concentration demonstrate the most significant enhancement in terms of Marshall stability and ITS. Conclusion: This correlation suggests that the incorporation of POFA, garnet waste, and sawdust as hybrid materials in the hybrid asphalt mixture possesses a positive effect on the overall mechanical properties of the pavement. Highlights: • POFA, garnet waste, and sawdust increased the stability of the hybrid asphalt mixture. • POFA, garnet waste, and sawdust increased the tensile strength of the hybrid asphalt mixture. • Hybrid asphalt mixture performs positively towards flow and stiffness.